The Relationship between the Leadership Style of Nurse Managers and the Performance of Health Cadres - Didin Syaefudin; Ita Ita; Lilis Kamilah (Indonesian Journal of Global Health Research, 2026)
The leadership style adopted by nurse managers in community health centers plays a crucial role in determining the performance of health cadres. Effective leaders can increase team motivation, engagement, and productivity, leading to the success of community-level health programs. Therefore, it is important to analyze the relationship between nurse managers' leadership style and the performance of health cadres in community health centers. This study aims to analyze the relationship between the leadership style of managing nurses and the performance of health cadres at Community Health Center X, Sukabumi City. This study used an observational analytical design with a cross-sectional approach. The respondents were 50 health cadres at Community Health Center X. Leadership style was measured using the Leadership Style Questionnaire (LSQ), while health cadre performance was measured using the Job Performance Scale. Data analysis was performed using the Spearman test to examine the relationship between the two variables. Among the 50 health cadres, those supervised under a transformational leadership style showed the highest performance, with 64.3% rated as high performers. Cadres under transactional leadership mostly achieved moderate performance (50%), while cadres under laissez-faire leadership had the lowest performance, with 62.5% rated low and none rated high. A significant positive relationship was found between leadership style and cadre performance (r = 0.423; p = 0.003). This study concludes that transformational leadership style has a significant influence on improving the performance of health cadres at Community Health Center X.